The disorders of respiratory tract microbiota in children with respiratory diseases (literary review) - O.S. Koreniuk (Zaslavsky O.Yu., 2018)
The article presents the data of national and foreign literature about microbiocenosis of human body under normal and pathological conditions. Stages of respiratory tract colonization by microflora in different periods of childhood are considered. The information of numerous studies on lung microbiota is presented in comparison with the microbiocenosis of the upper respiratory tract. Experimental data confirming the presence of microflora in the lungs of a healthy person and a direct correlation between the microbiota of the upper and lower respiratory tracts are provided. One of the most important factors determining the state of the microbiota of the lung is microaspiration. The value of microbiocenosis of open cavities for the formation of mucosal immunity is shown. The scientific concept about the algorithm of functioning of colonization resistance of the mucous membranes is outlined. We considered the method to evaluate nasopharynx microbiocenosis and the degree of dysbiosis. Particular attention is paid to the microbiota of the upper and lower respiratory tract in children with repeated respiratory diseases, as well as in children with recurrent and chronic respiratory diseases. It is shown that the identification of the pathogen in the culture from the upper and lower respiratory ways does not necessarily indicate its role as a causative agent of acute bronchopulmonary disease. The evaluation of dysbiosis severity is needed. However, long persistence of the infectious agent in patients with acute bronchopulmonary diseases can lead to an imbalance of immune reactivity and the formation of a chronic bronchopulmonary inflammatory process. Increased airway colonization in patients with chronic respiratory diseases is an important risk factor contributing to the development of exacerbations. It is noted that monitoring of etiologically significant microorganisms in patients with acute and chronic bronchopulmonary pathology is necessary for the improvement of pathogenetic treatment and prevention of chronic conditions.